2015
DOI: 10.1021/acs.energyfuels.5b01123
|View full text |Cite
|
Sign up to set email alerts
|

Gasification Kinetics of Biomass- and Fossil-Based Fuels: Comparison Study Using Fluidized Bed and Thermogravimetric Analysis

Abstract: In this work, the influence of experimental setup on derived kinetic data for the heterogeneous Boudouard gasification reaction is studied. A thermogravimetric analyzer (TGA) and a small-scale fluidized bed reactor (FBR) are used. The two systems differ basically in their fuel heating rates and fuel bed configurations. The kinetic study was performed in both reactors for the same temperatures and partial pressures of CO 2 at ambient pressure using same-batch fuel samples (biomass, brown coal, and petcoke). Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…where Y coke is the mass fraction of carbon in the coke, which is approximately 0.85 for lignocellulosic biomass coke [51,52]. HHV coke then is approximately 30.80 MJ/kg.…”
Section: Mass Loss Historymentioning
confidence: 99%
“…where Y coke is the mass fraction of carbon in the coke, which is approximately 0.85 for lignocellulosic biomass coke [51,52]. HHV coke then is approximately 30.80 MJ/kg.…”
Section: Mass Loss Historymentioning
confidence: 99%
“…Besides, the au thors also mentioned that the difference in char reactivity in the flui dized bed reactor and in the TGA is less significant at higher gasification temperatures. Mueller et al [39] also reported that, during the gasifi cation of high volatiles coal char with CO 2 for temperatures above 1073 K, the fluidized bed reactor shows significantly higher carbon conversion rate and reactivity than the TGA. They explained this phe nomenon by thermal annealing during the heat up of the char particles in the TGA which decreases the reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [11,38,39] observed that the reactivity of char in gasification or combustion is dependent on the type of reactors. For instance, in the case of coal char gasification with CO 2 , the authors [38,39] agreed that the reaction rate is higher in the fluidized bed than in the TGA. Zeng et al [38] explained this phenomenon by the switching gas method in the TGA which leads to a non uniform CO 2 partial pressure at the beginning of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from these techniques, other researchers (Fennell et al, 2009;Gövert et al, 2017) have proposed using a bench-scale fluidised-bed reactor (FBR) with a fast-response gas analyser to investigate the kinetics of char combustion. This method can provide homogeneous temperature and bulk gas composition, high heating rates (around 10 4 K/s), sufficient residence time, flexible temperature and gas compositions and an approximate carbon mass balance (Kim et al, 2017;Li et al, 2015;Mueller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, this method relies on any reaction of the sample being inferred by measuring the gas composition rather than directly measuring the weight change of the sample itself, thus opening itself up to errors. It is also difficult to extract and quench fuel samples during a combustion experiment to permit the analysis of morphology and composition evolution, which are possible for EFR and DTR (Kim et al, 2017;Mueller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%